Kruppel like factor 16 promotes lung adenocarcinoma progression by upregulating lamin B2. Issue 4 (1st April 2022) - Jiao, Xiaodan; Gao, Weinian; Ren, Hongxin; Wu, Yanning; Li, Tiezhi; Li, Shujun; Yan, Hongjiang
ABSTRACT: Lung cancer is one of the most common causes of cancer-related death. In the past decade, the treatment and diagnosis of lung cancer have progressed significantly in early efforts to promote the survival of lung cancer patients. Kruppel like factor 16 (KLF16) is a zinc finger transcription factor that regulates a diverse array of developmental events and cellular processes. KLF16 is involved in the progression of various cancer types. However, the role of KLF16 in the development of lung cancer remains unknown. In this study, KLF16 was overexpressed in lung cancer samples. KLF16 downregulation inhibited lung cancer cell proliferation and migration. Conversely, KLF16 overexpression promoted lung cancer cell growth and invasion. Mechanistically, the expression level LMNB2 was suppressed by KLF16 knockdown and was promoted by KLF16 overexpression. The overall survival of patients with high LMNB2 levels was poor. Luciferase assays showed that KLF16 promoted the transcription activity of LMNB2 gene. Concomitantly, the expression level of LMNB2 was also higher in lung adenocarcinoma (LUAD) than in normal tissues, and its knockdown or overexpression can reverse the effect of KLF16 overexpression or knockdown on lung cancer cell proliferation, migration, and even tumorigenesis, indicating that LMNB2 also functions as an oncogene. In conclusion, KLF16 can be used as a potential therapeutic and preventive biomarker in lung cancer treatment and prognosis by actively regulating the expression of LMNB2. GRAPHICAL ABSTRACT: uf0001